Corporate governance implementation: a key instrument for effective administration and management of state-owned enterprises—a scoping review - Johannes, Fillemon Nadhipite; Hendriks, Chris; Maramura, Tafadzwa Clementine (Frontiers in Political Science, 2025)
BackgroundCorporate governance has become an increasingly important area of inquiry in recent years, as organisations worldwide strive to establish effective governance structures and processes that foster long-term prosperity.PurposeThis review aimed to explore the implementation of corporate governance in state-owned enterprises (SOEs).MethodsThe article adopted a qualitative research methodology, employing a scoping review approach. This involved systematically searching relevant databases, screening studies, extracting data, and performing analyses.ResultsThe search revealed that the effective implementation of corporate governance is attainable and can enhance the performance of state-owned enterprises (SOEs) and minimise their financial dependency. However, despite the potential benefits of effective implementation of corporate governance in SOEs, the study highlighted the challenges associated with its implementation. These challenges include the exclusion of investors from the governance framework, the regular oversight of policies and procedures for internal control, the lack of political will, and the absence of effective monitoring and enforcement mechanisms. Therefore, the study suggested that policymakers should provide a clear SOE purpose, improve SOE governance regulations, and enhance financing capacity.